南極産菌類及び藻類由来の不凍タンパク質の機能解析 - 肖, 楠; 花田, 祐一; Sushruta, Hakkimane; 西宮, 佳志; 近藤, 英昌; 津田, 栄; 星野, 保; Nan, Xiao; Yuichi, Hanada; Sushruda, Hakkimane; Yoshiyuki, Nishimiya; Hidemasa, Kondo; et al. (2010)
第32回極域生物シンポジウム ポスター発表 conference object